2018
DOI: 10.1002/slct.201702898
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Blend of Water, DES and Ultrasound for One‐Pot Knorr Pyrazole Synthesis and Knoevenagel‐Michael Addition Reaction

Abstract: A simple and convenient method for the tandem synthesis of 4, 4-(arylmethylene)-bis-(3-methyl-1-phenyl-1H-pyrazol-5-ol)s via 3-methyl-1-phenyl-5-pyrazolone from aldehyde, phenyl hydrazine and ethyl acetoacetate using combination of Deep Eutectic Solvent (DES) and ultrasound in water is described. Shorter reaction time, easy work up and comparably good yield of desired product are crucial features. One pot Knorr synthesis and Knovenagel-Michael reaction and use of water as solvent make this methodology an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Use of ultrasound generates important advantage like it decreases the necessary temperature and time for the reaction with excellent yield (Scheme 37). [110] …”
Section: Synthesis Of 44’‐(arylmethylene)‐bis(1‐h‐pyrazol‐5‐ol) Deriv...mentioning
confidence: 99%
“…Use of ultrasound generates important advantage like it decreases the necessary temperature and time for the reaction with excellent yield (Scheme 37). [110] …”
Section: Synthesis Of 44’‐(arylmethylene)‐bis(1‐h‐pyrazol‐5‐ol) Deriv...mentioning
confidence: 99%
“…Preliminary investigations have shown that the eutectic mixture ChCl/tartaric acid is an efficient catalyst for the synthesis of bis‐phenyl‐1 H ‐pyrazol‐5‐ols . Having this in mind, and considering that the pyrazol‐3‐one 7 is the intermediate for the obtention of the target tetrahydrodipyrazolopyridine derivatives, our initial studies focused on explore the capability of different DES for obtaining the compound 7 starting from hydrazine hydrate and ethyl acetoacetate (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…DES formed from ChCl and tartaric acid was found to be an efficient catalyst for the synthesis of 4,4-(arylmethylene)-bis(3-methyl-1-phenyl-1 H -pyrazol-5-ol)s by the condensation of ethyl acetoacetate, phenyl hydrazine, and benzaldehyde at RT. 189 The synthesis involved the Knorr pyrazole synthesis, which was followed by Knoevenagel–Michael addition reaction using water as the solvent. The generality of the method was studied using various aldehydes and DES was reused up to five cycles; the reaction is given in Scheme 17.…”
Section: Applications Of Hydrophilic Dess In Various Organic Reactionsmentioning
confidence: 99%